Conclusion of the ceremony - Mumbai Archive Project Team (Jio Institute, 2024)
At the end of the ceremony, before using it for this purpose. A cloth is held above the bride and groom like a canopy, and a pair of winnowing trays are placed on it. The couple is then tasked with finding various items on the trays without looking up.